ANALISIS KESALAHAN KATA KERJA DALAM KARANGAN ANALYTICAL EXPOSITION BAHASA INGGRIS - Hernalia Citra Dewi (Pujangga: Jurnal Bahasa dan Sastra, 2016)
ABSRTACTThe aim of this research is to know students’ ability in writing an English analytical exposition text. It is also toidentify the kind of errors and to percentage those errors. Research method that is used to analyze the error is themethod of collecting data through survey and the descriptive method to describe the error that is made by studentsin writing an English analytical exposition text. After the data had been analyzed, the writer concluded that out of20 research samples, error of addition is the most error made by the student. It is 29.09%. While, the lowest error iserror of ordering. It is 9.09%.Keywords: error analysis, English analytical exposition